Specific Clearance of Senescent Synoviocytes Suppresses the Development of Osteoarthritis based on Aptamer‐Functionalized Targeted Drug Delivery System. (27th January 2022) - Chen, Xiang; Zhang, Lei; Shao, Xiaoyan; Gong, Wang; Shi, Tianshu; Dong, Jian; Shi, Yong; Shen, Siyu; He, Yi; Qin, Jianghui; Lu, Jun; Jiang, Qing; et al.
Abstract: Age‐related diseases are among the leading causes of morbidity worldwide currently. Therefore, there is an urgent need to develop effective interventions to reduce aging. In mice, the selective elimination of senescent cells via senolytics extends the median lifespan and attenuates various age‐related diseases including osteoarthritis (OA). However, most classified senolytics may also affect non‐senescent cells because of their suboptimal specificity for senescent cells, which hampers the translation of senolytic therapies to human diseases. Precise targeting of senolytics to specific senescent cell types may help circumvent these potential hurdles. In the joints of OA, abundant senescent fibroblast‐like synoviocytes (FLSs) are observed in the synovium region, which can promote the degradation of chondrocytes. Here, an aptamer‐functionalized liposome (LS) is developed, which encapsulates with senolytics (dasatinib and quercetin, DQ), termed as CX3‐LS‐DQ. This CX3‐LS‐DQ exhibits high affinity for FLS, a reasonably long circulation time, minimal toxicity, and strong clearance ability in senescent FLS. In the OA mouse model, intra‐articular injection of CX3‐LS‐DQ effectively attenuates cartilage degradation in vivo. Overall, the FLS‐specific aptamer‐functionalized drug delivery system could act as a novel carrier for targeted drug delivery to the synovium, providing a foundation for potential clinical translation in OA therapy. Abstract : Senescent FLSs are increased and can promote chondrocyte degradation during osteoarthritis progression. Aptamer CX3, screened by the cell‐SELEX system, exhibits a remarkable ability to distinguish FLS from chondrocytes. Intra‐articular injection of CX3‐modified liposomes can induce the apoptosis of senescent FLS and suppress the progression of osteoarthritis, providing a potential strategy for osteoarthritis therapy in the clinic.